EFEKTIVITAS PEMBERDAYAAN MASYARAKAT MELALUI PENYALURAN DANA BANTUAN BAZNAS PROVINSI PAPUA - Nur Afrianti; Sahudi Sahudi; Nani Hanifah (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
Society Empowerment is one of the benchmarks to measure the society’s independence. Thus, in line with the objectives of National Zakat Board (Baznas), which are getting rid of poverty and initiating independence attitude for mustahiq (people who are eligible to receive alms), human empowerment through the donation distribution executed by Baznas of Papua Province is getting widely implemented. This action is expected to create mustahiqs who are dependable and helpful for their surroundings and have the potentials to be muzakki (zakat/alms payers). This study aims to find out the effectiveness level of human empowerment through the Papua Province Baznas donation distribution. The methodology of this study is qualitative method. The data obtained are primary and secondary data. The data collection techniques are interview, observation, and documentation by involving associated people or parties. The results of the study show that, first, Baznas of Papua Province performed some efforts by distributing the donation comprising the fields of economy, education, health, Islamic preach, and social/humanity. Secondly, the effectiveness of human empowerment through the Papua Province Baznas donation distribution indicates that (1) the number of poor people in Abepante is decreasing, (2) the efforts of improving people’s income in Abepante is increasing, (3) People’s concern in Abepante is growing, (4) groups’ independence level is improving, and (5) People’s social capacity and equal distribution in Abepante are rising.